IDENTIFICATION OF ECOSYSTEM SERVICES: RECOGNITION AND CHALLENGES FOR DEVELOPMENTAL PLANNING - Campos Rojas, Gabriel Gerardo (2022)
In this research, the identification of ecosystem services were analyzed as a contribution to the recognition of opportunities and challenges for developmental planning in the area, taking into account the inhabitants of the Greater Metropolitan Area of Costa Rica. A survey was applied in the central parks of the following cantons: La Unión, Atenas, Alajuela, San José, Heredia, Paraíso, Cartago, Poás, Mora, Santa Ana, and Santa Bárbara. The results showed that 94 % of the interviewed people consider that they obtain ecosystem services. This allows designing methods that integrate, within plans, programs and projects, ecosystem services as a transversal topic in the developmental planning processes. The most recognized services were those of greater dependence for the subsistence of the human being, and it was identified that the recognition of these services depends on the knowledge that the population has of their territory. Also, 87 % of the surveyed people identified threats to ecosystem services, which is an opportunity for the population to participate in the formulation and implementation of actions aimed at counteracting these threats. It was determined that in development planning it is necessary to design tools that link the identification of ecosystem services with the formulation of actions that contribute to economic and social well-being, aligned with ecological conservation.